N‐P utilization of Acer mono leaves at different life history stages across altitudinal gradients - Zhaopeng Song (Wiley, 2020)
Abstract The relationship between plants and the environment is a core area of research in ecology. Owing to differences in plant sensitivity to the environment at different life history stages, the adaptive strategies of plants are a cumulative result of both their life history and environment. Previous research on plant adaptation strategies has focused on adult plants, neglecting saplings or seedlings, which are more sensitive to the environment and largely affect the growth strategy of subsequent life stages. We compared leaf N and P stoichiometric traits of the seedlings, saplings, and adult trees of Acer mono Maxim and different altitudes and found significant linear trends for both life history stages and altitude. Leaf N and P content by unit mass were greatly affected by environmental change, and the leaf N and P content by unit area varied greatly by life history stage. Acer mono leaf N‐P utilization showed a significant allometric growth trend in all life history stages and at low altitudes. The adult stage had higher N‐use efficiency than the seedling stage and exhibited an isometric growth trend at high altitudes. The N‐P utilization strategies of A. mono leaves are affected by changing environmental conditions, but their response is further dependent upon the life history stage of the plant. Thus, this study provides novel insights into the nutrient use strategies of A. mono and how they respond to the environmental temperature, soil moisture content along altitude and how these changes differ among different life history stages, which further provide the scientific basis for the study of plant nutrient utilization strategy on regional scale.